Analysis of command, order and request directive speech act found in frozen 2 movie - Yani, Ni Kadek Windra; Maharani, Putu Devi (Journal of Language and Applied Linguistics, 2022)
Being a social human, people have a way to express their hopes, which produces a directive illocutionary act. Directive illocutionary acts are a fascinating phenomenon of illocutionary acts. This research used theory from Searle (1979) to find out the dominant three types of directive speech act, Leech theory (1983) about Aspect of Speech theory to analyzed the purpose of directive speech acts. The researcher used a descriptive qualitative approach to collect data, the data that are founds from the data source were analyzed by using formal and informal method to support the research. According to the findings of this study, there are three types of directive speech acts used by figures in Frozen 2 Movie, they are command (76%), order (11%), request (13%). The three dominant types have quite similar meaning but in this research the researcher try to analyses and find out their differences clearly